2018
DOI: 10.3390/molecules23071631
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Blue-Light-Induced Free Radical Formation from Catechin Hydrate on the Inactivation of Acinetobacter baumannii, Including a Carbapenem-Resistant Strain

Abstract: Catechin is a flavan-3-ol, a derivative of flavans, with four phenolic hydroxyl groups, which exhibits a wide range of physiological properties. Chromatographic analyses were employed to examine the effects of blue light irradiation on the changes of catechin hydrate in an alkaline condition. In particular, the detection of a superoxide anion radical (O2•−), a reactive oxygen species (ROS), and the inactivation of Acinetobacter baumannii (A. baumannii)—including a carbapenem-resistant A. baumannii (CRAB)—was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(64 citation statements)
references
References 45 publications
2
60
0
Order By: Relevance
“…As reported by previous works in our lab, increased oxidative stress by plant extracts and phytochemicals reduced the intracellular ATP levels [22]. Yang et al reported that light-activated CA caused increased DNA strand breakage resulting in the depletion of cellular NAD + and ATP levels leading to cell death [23]. The nuclear damage observed in A549 cells by CA and PDT through Hoechst staining is in correlation with the observed morphological changes in the treated cells revealing cytotoxicity and cell death.…”
Section: Discussionsupporting
confidence: 82%
“…As reported by previous works in our lab, increased oxidative stress by plant extracts and phytochemicals reduced the intracellular ATP levels [22]. Yang et al reported that light-activated CA caused increased DNA strand breakage resulting in the depletion of cellular NAD + and ATP levels leading to cell death [23]. The nuclear damage observed in A549 cells by CA and PDT through Hoechst staining is in correlation with the observed morphological changes in the treated cells revealing cytotoxicity and cell death.…”
Section: Discussionsupporting
confidence: 82%
“…Liang et al reported that riboflavin or FMN treated with blue light illumination produced a large amount of O 2 • − that degraded crystal violet [ 14 ] and led to the inactivation of E. coli and MRSA through ROS formation [ 3 , 13 , 30 ]. It has been reported that catechin hydrates under blue light illumination, and O 2 • − was generated from photo-oxidation, increasing the inactivation rate of A. baumannii , including the carbapenem-resistant, A. baumannii [ 12 , 50 ]. The O 2 • − generation in cells may induce DNA degradation, membrane peroxidation, and the destruction of endothelial cells [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both direct and indirect methods can be utilized to detect active O 2 • − . The direct method requires particular apparatus, such as an electron spin resonance (ESR) spectroscopy, while the indirect ways are easily exercised in analysis [ 12 ]. The nitro blue tetrazolium (NBT) reduction method is an indirect assay for determining O 2 • − , and NBT can be reduced by the O 2 • − from intermediates [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The next paper [3] comes from the laboratories of Iou-Zen Chen and Ji-Yuan Liang in Taiwan. These authors studied a flavan-3-ol called catechin as a blue-light activated photosensitizer to kill Gram-negative bacteria Acinetobacter baumannii and a carbapenam-resistant variant.…”
mentioning
confidence: 99%